(untitled) (Bangladesh Journal of Child Health, 2018)
Congenital pulmonary airway malformation (CPAM) is a very rare congenital cystic lung disease in children. Frequent respiratory tract infections (RTI) are major concerns in these patients. When a child having recurrent episodis of RTI, CPAM could be the underlying pathology. Surgical excision is recommended to make a definite diagnosis and exclude hidden malignancies and is also the treatment of choice. Here in, we report a 6 months old girl presenting with an acute respiratory infection for the first time. An routine USG of abdomen incidentally showed multiple cystic lessions in the left lower lung. CT scan of chest also revealed similar lessions in some area. After receiving treatment for pneumonia surgical excision was performed and she was doing well after surgery Bangladesh J Child Health 2017; VOL 41 (2) :129-134